(untitled) (International Journal of Scientific Research in Science and Technology, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in fostering rural economic development by creating employment opportunities, enhancing income levels, and promoting entrepreneurship. This study examines the impact of MSMEs on rural livelihoods in Bihar, a state with a significant rural population and economic dependence on agriculture and small industries. By analyzing various dimensions such as job creation, income generation, skill development, and financial inclusion, this research highlights the transformative role of MSMEs in rural communities. The study utilizes both primary and secondary data sources to assess the contribution of MSMEs in improving the socio-economic conditions of rural Bihar. A sample of MSME entrepreneurs, workers, and policymakers was surveyed to understand the challenges and opportunities within the sector. Key findings suggest that MSMEs significantly enhance rural livelihoods by reducing unemployment, providing skill-based training, and fostering self-reliance among rural populations. However, challenges such as inadequate financial support, infrastructural gaps, and policy inefficiencies hinder their full potential. The study concludes that strengthening MSMEs through policy reforms, better financial access, and infrastructural development can further accelerate economic progress in rural Bihar. The research provides valuable insights for policymakers, business leaders, and development practitioners to harness the full potential of MSMEs for sustainable rural growth.